May Measurement Month 2022: an analysis of blood pressure screening results from Colombia (2025)
The May Measurement Month (MMM) campaign was carried out in Colombia in 2022 with the aim of raising awareness of raised blood pressure (BP). Here, we report on the findings of the campaign. Adults aged ≥ 18 years were recruited opportunistically at healthcare and public facilities in eleven departments. Three seated BP readings were taken for each participant, along with completion of a questionnaire on demographics, lifestyle factors, and comorbidities. Hypertension was defined as a systolic BP ≥ 140 mmHg and/or diastolic BP ≥ 90 mmHg or being on antihypertensive medication. Controlled BP was defined as being on antihypertensive medication with a BP <140/90 mmHg. Multiple imputation was used to estimate any missing BP readings. In total, 38 924 were screened, with a mean age of 46.3 years and 52.9% of whom were female. Of all participants, 10 738 (27.6%) had hypertension, of whom 7058 (65.7%) were aware, and 6925 (64.5%) were on antihypertensive medication. Of those on antihypertensive medication, 4600 (66.4%) had controlled BP, and of all participants with hypertension, 42.8% had controlled BP. However, those under 50 years had lower hypertension control (<30%). Women had a higher BP control than men (49.5 vs 36.3%). High education was associated with lower systolic BP (-2.37 mmHg). The MMM campaign in Colombia identified significant numbers of participants with either untreated or inadequately treated hypertension. MMM22 results point to the need to continue improving awareness and seek a broader implementation of strategies with proven efficacy in controlling hypertension.